Utilisation of community pharmacists by the general public in Malaysia - Chua, S.S.; Lim, K.P.; Lee, H.G. (2013)
OBJECTIVES: The study was conducted to assess how the general public in the Klang Valley, Malaysia, utilised community pharmacists. METHODS: This was a prospective observational study which documented interactions between community pharmacists and their customers. A researcher was stationed in 10 participating community pharmacies around the Klang Valley to observe and record all the interactions, using a structured data-collection form. KEYS FINDINGS: Interactions between 1914 customers and the pharmacists of the 10 community pharmacies were recorded. A total of 2199 requests were made by these customers. The main types of request were for medications by brand name (32.2), advice on minor health problems (25.9) and for health supplements (11.7). Only 65 prescriptions were received by the community pharmacies; that is, fewer than two prescriptions per pharmacy per day. The pharmacists provided counselling for only 54.4 of the requests where a medication or health supplement was dispensed. Counselling by pharmacist was significantly associated with the type of request (P < 0.001). CONCLUSIONS: The main reason for the general public to visit a community pharmacy in Malaysia was to purchase a particular medication. Few prescriptions were filled at community pharmacies in Malaysia, indicating the under-utilisation of community pharmacists as a safety net for prescribed medications in primary care.